Use of plasmapheresis and intravenous immunoglobulins in pregnant women with antiphospholipid syndrome - E. S. Orlova; S. V. Chepanov; M. S. Zainulina; S. A. Selkov (Медицинская иммунология, 2025)
Our objective was to demonstrate the efficiency of therapy for antiphospholipid syndrome (APS) in pregnant women using plasmapheresis and intravenous immunoglobulins.92 women with diagnosed APS and 47 APS-free women with physiological pregnancy were under study. APS was diagnosed in accordance with Sydney Consensus Workshop (2006). Patients with APS were divided into groups depending on the method of treatment used: conventional therapy, plasmapheresis in addition to standard therapy, intravenous immunoglobulins (IVIG) in addition to standard therapy, and complex treatment, i.e., plasmapheresis and IVIG added to standard therapy. The levels of antiphospholipid antibodies, hemostasis parameters, P-selectin were measured in blood serum and plasma before and after treatment.Higher frequency of favorable pregnancy outcomes was shown in the group of patients with APS who were treated with combined therapy, i.e. in 96.3% of cases (term birth). Frequency of prematurity and fetal hypotrophy was significantly lower in the group of patients with APS treated with combined therapy. The most significant decrease in the level of antiphospholipid antibodies was observed in the group treated by plasmapheresis, IVIG and conventional therapy. Expression of P-selectin in the women with normal pregnancy without antiphospholipid antibodies, was significantly lower compared to pregnant women with APS.Usage of integrated approach using plasmapheresis, intravenous immunoglobulins and standard therapy is the most effective treatment for APS-related miscarriage. Implication of this strategy has reduced the incidence of obstetric complications and improved pregnancy outcomes due to increased frequency of term births, as well as lowest indices of pathology in the newborns. Analysis of P-selectin levels before and after treatment enables determination of the platelet activation levels, efficiency of therapeutic approaches, as well as medical drug correction of infavorable platelet hemostasis during therapy.